Platyhypnidium aquaticum as bioindicator of metal and metalloid contamination of river water in a neotropical mountain city - Benítez, Angel (2020)
Water contamination is a major environmental problem in many cities of the world. Most water contamination results from industry and human activities that generate toxic substances (e.g., metals). Rheophilic and aquatic mosses are found in lotic ecosystems, and their morphological and physiological traits are responsive to ecological and pollution gradients. Here we hypothesized that the native rheophilic moss Platyhypnidium aquaticum (A. Jaeger) M. Fleisch exposed to polluted waters can bioaccumulate greater amounts of metals, and a metalloid, than P. aquaticum exposed to pollution-free water. To this aim, we tested the bioindicator capacity of the aquatic P. aquaticum for 15 metals (Cd, Pb, Zn, Fe, K, Ca, Na, Mn, V, Co, Ba, Cr, Al, Sr, and Mg) and one metalloid (As), in twelve river samples coming from three urban and one control zone along the Zamora river in the city of Loja. When compared to the control, our results showed that P. aquaticum in the Southern, Central, and Northern zones of the city bioaccumulated higher concentrations of Ba, Cd, Co, Fe, Mg, Mn, Na, Sr, Zn, and the metalloid As. On the other hand, concentrations of Al, Ca, Cr, Pb, and V in P. aquaticum tended to be lower in the control zone, but these differences were not significant. We suggest that the presence of these contaminants may be related to water pollution (e.g., residual discharges and a lack of treatment systems) along urban zones of the river. We report for the first time the utility of P. aquaticum as a model species for development of long-term biomonitoring programs of water contamination in South America. Passive biomonitoring with P. aquaticum can be a simple and low-cost method to obtain reliable data of the current state of water contamination with metals and metalloids in tropical regions. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.